Performance Comparison of EKF/UKF/CKF for the Tracking of Ballistic Target - Dai Hong-de; Dai Shao-wu; Cong Yuan-cai; Wu Guang-bin (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
This paper considers three well know nonlinear Kalman Filters for the tracking of a ballistic target. Extended Kalman Filter (EKF), Unscented Kalman Filter (UKF), and the Cubature Kalman Filter (CKF) are applied for estimating the position, velocity and the ballistic coefficient of the ballistic target. The theory formulation and computer simulation has been done for the comparison of the three nonlinear Kalman Filters. Results show that all of them can accomplish the estimation task, but the UKF and CKF both have higher accuracy and less computation cost than the EKF. DOI: http://dx.doi.org/10.11591/telkomnika.v10i7.1564